Advances in Chemical Conjugation of Natural Cysteine: Techniques and Applications - Xu, Kaibo; Li, Jinling; Zhang, Zhenguo; Loh, Teck-Peng (Synlett, 2025)
This review examines recent progress in chemical modification of natural cysteine residues, emphasizing biomedical and biotechnological applications. Capitalizing on the distinctive thiol group of cysteine (-SH) and natural scarcity in proteins, researchers have developed selective modification strategies operating under physiological conditions. The analysis systematically compares single thiol functionalization techniques (maleimide conjugation, cyclooctyne reactions) and disulfide rebridging approaches (phosphonamidate/allenamide linkers), evaluating their respective merits and limitations. Current applications span targeted drug delivery, biosensor development, and protein engineering innovations. The discussion highlights increasing attention toward disulfide bond manipulation for enhanced bioconjugation stability and diversity. While acknowledging the transformative potential of the field, the review identifies key challenges in the optimization of reaction specificity, product stability, and biological compatibility that will guide future research directions.1 Introduction2 Single Thiol Functionalization of Cysteine3 Disulfide Functionalization of Cysteine4 Conclusion
Keywords: cysteine modification; bioconjugation; single thiol functionalization; disulfide rebridging; biomedical applications